PERAN DOKTER KECIL DALAM PENANGANAN KEDARURATAN TRAUMA DENTAL DENGAN METODE SIMULASI - Annisa Indita Riami; Sri Wahyuni; Bertha Aulia (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2018)
The world statistic showed the prevalence of dental trauma in children in many countries was 25%. Out of cases, 97,55% were untreated and caused disablement. The location of the second highest dental trauma occurrence was school (41%). Dokter kecil as school health worker was expected to perform emergencymanagement of dental trauma before it was done by medical professionals, therefor educational intervention with a proper method was needed. To determine dokter kecil’s role in dental trauma emergency management using simulation method.The subjects were 60 dokter kecil who were divided into 2 groups; 30 dokter kecil group of simulation method and 30 dokter kecil group of demonstration method. Knowledge of dental trauma emergency treatment before and after intervention of each group were measured using a questionnaire totaling 17 questions. Data analysis used in this study was paired T test. Simulation method increased the average knowledge of dokter kecil by 55,6%, while demonstration method 46,6%. Paired T test results of the comparison simulation and demonstration method was p-value=0.031 (p-value <0.05). Conclusions: Education of dental trauma emergency management using simulation method was more effective than demonstration method to improve dokter kecil’s knowledge